Parallel conjugate gradient method - Čiegis, Raimondas; Šilko, Galina (Lietuvos matematikos rinkinys, 2003)
We investigate a parallel version of the preconditioned conjugate gradientmethod. A scalability analysis is done for a finite difference schemewhich approximates the 3D elliptic problem. Results of numerical experiments are presented which confirm theoretical conclusions.